If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 22 = n + 16 Combine like terms: 5 + 22 = 27 27 = n + 16 Reorder the terms: 27 = 16 + n Solving 27 = 16 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 27 + -1n = 16 + n + -1n Combine like terms: n + -1n = 0 27 + -1n = 16 + 0 27 + -1n = 16 Add '-27' to each side of the equation. 27 + -27 + -1n = 16 + -27 Combine like terms: 27 + -27 = 0 0 + -1n = 16 + -27 -1n = 16 + -27 Combine like terms: 16 + -27 = -11 -1n = -11 Divide each side by '-1'. n = 11 Simplifying n = 11
| 2(3x-1)=3-(-2-x) | | 3w+16=7w | | 12*x+6=-228 | | x*5+8=7 | | 8+2(8x-6)=16x+4 | | Xy+xz=1 | | f(x)=2x^2+12 | | 3x+32=56 | | 5(b+3)=3b+23 | | 3x-8=56 | | 4x+9-2x+2=3x-5-x | | 12-6x=2x+10 | | 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 |